2017
DOI: 10.1016/j.jsps.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the immunomodulatory activities of Sarcodon imbricatus extracts in a cyclophosphamide (CTX)-induced immunosuppressanted mouse model

Abstract: , an edible fungus, is widely used in Asian medicine because of its significant pharmacological activities. In the present study, we investigated the immunomodulatory effects of polysaccharide-enriched extracts (SP) in cyclophosphamide (CTX)-induced immunosuppressed mice. polysaccharide (AP) was used as a positive control. Compared with CTX-induced immunosuppressed mice, thirty-day SP treatment strongly enhanced the organ indexes of spleen and thymus and suppressed hind paw swelling. Both AP and SP increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 33 publications
3
21
0
Order By: Relevance
“…Cy is an important alkylating agent used in cancer treatment and blood and marrow transplantation [21]. However, the administration of Cy can lead to immunosuppression and hepatotoxicity that is reflected in lower body weight and spleen and thymus indices, disruption of the intestinal mucosal immunity, liver dysfunction, and oxidative stress [22,23]. Thus, Cy was used to creating the immunosuppressed animal model in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Cy is an important alkylating agent used in cancer treatment and blood and marrow transplantation [21]. However, the administration of Cy can lead to immunosuppression and hepatotoxicity that is reflected in lower body weight and spleen and thymus indices, disruption of the intestinal mucosal immunity, liver dysfunction, and oxidative stress [22,23]. Thus, Cy was used to creating the immunosuppressed animal model in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcodon imbricatus (L.) P. Karst, belonging to the family Bankeraceae, is an edible fungus occurring in China, Thailand, and Turkey [4,58,215]. It is widely used in Asian medicine [216]. An investigation on a polysaccharide-enriched extract of S. imbricatus revealed that it stimulates the immune response in CTX-induced immunosuppressed mice via modulation of oxidative pathways [216].…”
Section: Sarcodon Imbricatus (L) P Karstmentioning
confidence: 99%
“…It is widely used in Asian medicine [216]. An investigation on a polysaccharide-enriched extract of S. imbricatus revealed that it stimulates the immune response in CTX-induced immunosuppressed mice via modulation of oxidative pathways [216]. An extract of S. imbricatus exhibited the growth of gram-negative and gram-positive bacteria [22,217].…”
Section: Sarcodon Imbricatus (L) P Karstmentioning
confidence: 99%
See 1 more Smart Citation
“…Mushrooms are well‐known for their nutritional content and are predominantly consumed worldwide for their health and nutritional benefits. Scaly‐tooth mushroom, Sarcodon imbricatus (L.) P. Karsten, is a valuable edible mushroom known for its nutritional and medicinal values . This edible basidiomycete fungus belongs the Division: Basidiomycota, Class: Agaricomycetes, Order: Thelephorales and is commonly found symbiotic association with Norway spruce and pine widely distributed in north America and Europe.…”
Section: Introductionmentioning
confidence: 99%